Meaning-Making, Psychological Distress, and the Experience of Meaning in Life Following a Natural Disaster. Issue 5 (July 2021) - Maffly-Kipp, Joseph; Flanagan, Patricia; Kim, Jinhyung; Rivera, Grace; Friedman, Matthew D.; Vess, Matthew; Hicks, Joshua A.
The purpose of this study was to examine the role of meaning-making in response to collective trauma. In the aftermath of Hurricane Harvey, we recruited participants ( N = 570) to test the hypothesis that searching for meaning (vs. finding meaning) in the event would be associated with greater (vs. lower) levels of acute and post-traumatic stress symptoms. We further hypothesized that searching for (and finding) meaning in the event would predict global search for (and presence of) meaning in life (MIL). Consistent with our hypotheses, we found that searching for meaning in the event was associated with greater psychological distress at both time points and predicted global search for MIL at one of the time points. Finding meaning in the event was unexpectedly not consistently associated with lower levels of stress; however, across analyses, finding meaning in Hurricane Harvey was associated with greater levels of MIL. Implications and possible explanations for these unexpected results are discussed.